Pengabdian Kepada Masyarakat Sosialisasi Asuransi pada Generasi Z di SMA Dewi Sartika Tebet Jakarta Selatan: Pengabdian - Muhammad Nasyubin; M Agung Akhdani (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This training or socialization aims to provide understanding about insurance among Generation Z. It is expected that through the establishment of this insurance literacy association, Generation Z will become more educated and gain a better understanding of the importance of insurance for their generation.The participants of the socialization activity gained a clearer understanding of the basic concepts, definitions, and meanings of insurance. This initiative is intended to build awareness about what insurance is, especially for the younger generation (Gen Z) at Dewi Sartika Senior High School.During the session, participants were introduced to various types of insurance in general, helping them recognize different types of insurance and understand their distinctions.Through this insurance literacy socialization, participants acquired the knowledge and awareness that insurance is an important tool for young people (Gen Z), helping them become more “literate” and concerned about insurance matters.